An international comparison of lifetime inequalilty: How Continental Europe resembles North America - Audra J. Bowlus; Jean-Marc Robin (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
We compare earnings inequality and mobility across the U.S., Canada, France, Germany and the U.K. during the late 1990s. A flexible model of earnings dynamics that isolates positional mobility within a stable earnings distribution is estimated. Earnings trajectories are then simulated, and lifetime annuity value distributions are constructed. Earnings mobility and employment risk are found to be positively correlated with base-year inequality. Taken together they produce more equalization in countries with high cross-section inequality such that the countries in our sample have more similar lifetime inequality levels than crosssection measures suggest.
Keywords: 330; Einkommensverteilung; Soziale Mobilität; Beschäftigung; Risiko; Lebenseinkommen; USA; Kanada; EU-Staaten